2011
DOI: 10.1007/s12031-011-9633-0
|View full text |Cite
|
Sign up to set email alerts
|

Interkinetic Nuclear Movement in the Ventricular Zone of the Cortex

Abstract: The nuclei of neuroepithelial cells move along the apicobasal axis in synchronization with their cell cycle status. This motility is known as interkinetic nuclear movement. We discuss here the importance of cytoskeleton organization, the centrosome, molecular motors, cell polarity proteins, and their regulators in controlling and maintaining this typical behavior. Furthermore, due to the tight linkage between cell proliferation, cell cycle, and nuclear motility, we speculate that interkinetic nuclear movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 99 publications
0
29
0
Order By: Relevance
“…Disrupting the maintenance of adherens junctions impairs the Wnt pathway, shortens cell cycle and induces early neuronal differentiation. Both the apically localized Numb and β-catenin are negatively correlated with neuronal differentiation; that is, their constitutive expression results in decreased differentiation, and their reduction leads to decreased cell proliferation (Reiner et al, 2012). Likewise, the PAR complex is positively associated with maintaining a proliferative fate (Cappello et al, 2006; Costa et al, 2008; Bultje et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Disrupting the maintenance of adherens junctions impairs the Wnt pathway, shortens cell cycle and induces early neuronal differentiation. Both the apically localized Numb and β-catenin are negatively correlated with neuronal differentiation; that is, their constitutive expression results in decreased differentiation, and their reduction leads to decreased cell proliferation (Reiner et al, 2012). Likewise, the PAR complex is positively associated with maintaining a proliferative fate (Cappello et al, 2006; Costa et al, 2008; Bultje et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this region, neural progenitors exhibit elevator-like, to-and-fro nuclear movements called interkinetic nuclear migration (INM) (Schaper, 1897;Sauer, 1935;Sauer and Walker, 1959;Sidman et al, 1959;Fujita, 1962). Studies of the mechanisms underlying INM have shown that both microtubuleand actomyosin-dependent mechanisms are involved (reviewed in Miyata, 2008;Taverna and Huttner, 2010;Kosodo, 2012;Reiner et al, 2012;Spear and Erickson, 2012;Lee and Norden, 2013). One of the essential roles of INM is prevention of overcrowding in the VZ, thereby ensuring the aforementioned normal segregation between neurons and progenitors, as well as subsequent formation of ordered neuronal layers (Okamoto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei of VZ progenitors are positioned at basal (abventricular) locations in the VZ during S phase, move towards the apical surface (the ventricle side) during G2 phase, undergo mitosis (M phase) at the apical (ventricular) surface and return towards basal positions in G1 phase; this oscillation process is called interkinetic nuclear migration (INM) 10,36,37 (FIG. 2a).…”
Section: Molecular Mechanisms Of Cortical Growthmentioning
confidence: 99%